OPTIMASI PEMBUATAN BIOPELLETS DARI BUNGLCII PICUNG ( PANGIUM EDULE REINW) DENGAN PENAMBALIAN SOLAR DAN PERELCATTAPIOLIA - Akhyarali '; Fajar Restuhadi (Universitas Riau, 2010)
Picung seeds Pangium edule Reinw; contain 70% kernel (ireight) and 40% Imsk (weight). Itsnucleus seeds contain 21-27% oib that can be extracted. More than iia 70% cmqionait is oil cake. The hugeamount of oil cake can be used as a solid fuel sucb as biopellets. Picung biopelleis are produced by usinghydraulic press hi the form of solid pieces with a specific size. Picung oil cakes need to be unifDnidy distributedas a soUd piece. Therefore, it needs to be bound and unified as a solid piece. Bhiding problems can be solvedby adding tapkxs. Optunum addition of tapioca is not more than 5%. However, adding tapioca wiU reduce theburning caloric properties of the bio-pellets. To increaM the caloric properties, diesel-oil can be added,because diesel oil has high caloric value equal to 7020 kcaVkg. Thefinalstep of this research was to optimizethe composition of tapioca and bio-diesel blends to produce the bio-pellets which satisfies the IndonesianNational Standard (SNI) with the highest caloric value. The cntral composit des^ w » used ftr the experiment.Thefirstfactor (X,) was quantity of solar (ml) and the second factor (X,) was quantity of tapioai (gran^. Firstfactor's range were between 1 to 53 % (l/w) diesel oil over picung cake or 2,<i9-17,33 ml diesel oH. Thesecond factor range was I to 5 % (w/w) diesel oil over picung cake. Optimization response used b heatingcaloric value of the bk>-pellcts (Y). Analysis with response surface method shows that bio-diesel addition haspositive influence to the heating caloric value of biopellets with desirability of0,840. The optimum value forheating calor biopellets is 6117,78 kril/kg.",